(untitled) (Journal of Computational Mathematics, 2018)
In the present paper the edge stabilization technique is applied to a convection-diffusion problem with exponential boundary layers on the unit square, using a Shishkin mesh with bilinear finite elements in the layer regions and linear elements on the coarse part of the mesh. An error bound is proved for ||πu−u^h||_E where πu is some interpolant of the solution u and u^h the discrete solution. This supercloseness result implies an optimal error estimate with respect to the L_2 norm and opens the door to the application of postprocessing for improving the discrete solution.